Pengaruh Supervisi dan Gaya Kepemimpinan Kepala Madrasah Terhadap Kinerja Pendidik Tenaga Kependidikan - Mukhlisin Mukhlisin (Departement of Mathematics Education, 2024)
The main problem in this study is how the influence of supervision and leadership style together with the Head of Madrasah on the performance of educators and education staff in MTsN 2 Serang City?. while the main purpose of this study is to determine the influence of supervision and leadership style together with the Head of Madrasah on the performance of educators and education staff in MTsN 2 Serang City.The method used in this study is a correlational quantitative method with research instruments: questionnaires, interviews and documentation. This research was conducted in MTsN 2 Serang City, with a population of 43 respondents, so the researchers took all of them as research samples. The results of this study show that there is a significant relationship between the supervision of the head of the madrasah and the leadership style together on the performance of educators and education staff in MTsN 2 Serang City. With the magnitude of the contribution of the two independent variables to the dependent variable of 68.89%. While the remaining 31.11% is influenced by other factors that can be further investigated.